Climate governance and urban planning : implementing low-carbon development patterns - Heinen, Deborah (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Urban planning as a discipline is deeply integral to implementing a low-carbon future. This book fosters an understanding for the rules-in-use that govern urban planning and influence the ability to implement low-carbon development patterns. Drawing on the theoretical foundations of the climate governance and urban planning literatures, the book provides a context to understand plan implementation challenges and obstacles in metropolitan areas. A particular planning challenge in metropolitan regions is examined in depth as an example to understand the polycentric nature of taking climate actions: The challenge to implement transit-connected urban centers. As metropolitan regions across the globe seek to reduce emissions from transportation, many levels of governments have developed ambitious climate action plans that make land use and transportation recommendations in order to reduce vehicle miles traveled. Many have recommended low-carbon development patterns which are characterized by intensified and diversified uses around rapid transit stations. However, the implementation of these recommendations is done within the context of different "rules-in-use" unique to the planning systems in the metropolitan region. The book examines the rules-in-use around the many actors involved in implementing low-carbon development patterns in three metropolitan regions of similar demographic size. By examining the implementation of low-carbon development patterns, the book focuses on growth management related questions about how to coordinate transit investments with land use decisions in metropolitan regions. The book finds that state legislation that deals with metropolitan planning and regional growth strategies can greatly aid in creating accountability among actors as well as provide a road map to navigate conflicts when implementing low-carbon development patterns. By focusing on the rules-in-use, the book is of interest to policy makers, planners, advocates, and researchers that wish to assess and improve the odds of implementing low-carbon development patterns in a metropolitan region"--
Keywords: City planning; Carbon dioxide mitigation -- Government policy; BUSINESS & ECONOMICS / Environmental Economics; BUSINESS & ECONOMICS / Urban & Regional